Authentic Leadership and Behavioral Integrity as Drivers of Follower Commitment and Performance - Leroy, Hannes; Palanski, Michael E.; Simons, Tony (2012)
The literatures on both authentic leadership and behavioral integrity have argued that leader integrity drives follower performance. Yet, despite overlap in conceptualization and mechanisms, no research has investigated how authentic leadership and behavioral integrity relate to one another in driving follower performance. In this study, we propose and test the notion that authentic leadership behavior is an antecedent to perceptions of leader behavioral integrity, which in turn affects follower affective organizational commitment and follower work role performance. Analysis of a survey of 49 teams in the service industry supports the proposition that authentic leadership is related to follower affective organizational commitment, fully mediated through leader behavioral integrity. Next, we found that authentic leadership and leader behavioral integrity are related to follower work role performance, fully mediated through follower affective organizational commitment. These relationships hold when controlling for ethical organizational culture.
Keywords: Work role performance; Ethical organizational culture; Behavioral integrity; Authentic leadership; Affective organizational commitment